2016
DOI: 10.1063/1.4959880
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ageing on Raman spectra and the conductivity of monolayer graphene samples irradiated by heavy and light ions

Abstract: The influence of long-term ageing (about one year) on the Raman scattering (RS) spectra and the temperature dependence of conductivity has been studied in two series of monolayer graphene samples irradiated by different doses of C + and Xe + ions. It is shown that the main result of ageing consists of changes in the intensity and position of D-and G-and 2D-lines in RS spectra and in an increase of the conductivity. The observed effects are explained in terms of an increase of the radius of the "activated" area… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…The value of k reflects the average fraction of carbon vacancies in the graphene lattice per ion impact. For C + ions with M = 12 in atomic mass units (amu) and for Xe + ions (M = 131 amu) with E = 35 keV, k = 0.06-0.08 and 0.8 correspondingly [10]. The changes in the intensities of both D-and 2D-lines ID and I2D with increase of Nd in these samples were studied in [10][11][12].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The value of k reflects the average fraction of carbon vacancies in the graphene lattice per ion impact. For C + ions with M = 12 in atomic mass units (amu) and for Xe + ions (M = 131 amu) with E = 35 keV, k = 0.06-0.08 and 0.8 correspondingly [10]. The changes in the intensities of both D-and 2D-lines ID and I2D with increase of Nd in these samples were studied in [10][11][12].…”
Section: Methodsmentioning
confidence: 99%
“…For C + ions with M = 12 in atomic mass units (amu) and for Xe + ions (M = 131 amu) with E = 35 keV, k = 0.06-0.08 and 0.8 correspondingly [10]. The changes in the intensities of both D-and 2D-lines ID and I2D with increase of Nd in these samples were studied in [10][11][12]. It was shown that I2D continuously decreases, while ID first increases and then decreases, the maximal value is achieved at Nd ≈ 4x10 12 cm -2 , which corresponds to the mean distance between defects Ld ≈ (Nd) -1/2 ≈ 5 nm.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Details of sample preparation, ion irradiation and measurements of RS in our samples before annealing were reported in our previous papers 22,23 . Two initial large scale monolayer graphene specimens (5x5 mm) were supplied by Graphenea Inc.. Monolayer graphene was produced by CVD on copper catalyst and transferred to a 300 nm SiO 2 /Si substrate using wet transfer process.…”
Section: Samplesmentioning
confidence: 99%